دور التسويق الرقمي في صناعة السياحة دراسة حالة فندقي الماريوت وهيلتون - حبيبة, قيطون; خديجة, بالهادف (University of eloued جامعة الوادي, 2022)
"تهدف هذه الدراسة لإبراز التسويق الرقمي كواقع فرض نفسه بقوة في السوق العالمية لصناعة السياحة ،وذلك بتثمين الدور الذي يلعبه في توليد استراتيجيات مستقبلية رقمية ابتكارية، والتي من خلالها يمكن وضع تصور لطوير وتنمية صناعة السياحة وبالتالي تفعيل وتنشيط هذا القطاع مع تهيئته للتحول لنمط السياحة الرقمية. اعتمدنا في الدراسة التطبيقية على فندقين دوليين رائدين في قطاع الضيافة وتوصلنا الى انه لتطوير صناعة السياحة لابد من خلق استراتيجية تسويقية مدروسة ومخصصة ودقيقة عبر وسائل التواصل الاجتماعي، لان الاتصالات الاجتماعية الفعالة يمكن ان تجلب المشاركة وخدمة العملاء الفائقة لدعم العملاء، نظرا لارتفاع تكاليف اكتساب العملاء من خلال الاعلانات التقليدية عبر الانترنت، يجب على المستثمرين في صناعة السياحة ان تقيم حقا عائد الاستثمار لجذب مستهلكين جدد الى حلقة الولاء التي قد تفقد بصمة الاحتفاظ بالمستهلكين فعليا ، وكذا يجب على اصحاب الفنادق انتاج محتوى دائم التشغيل ليس فقط وثيق الصلة بالموضوع، ولكنه يرتكز على خصوصيات وجهة محلية، وانشاء روابط لوضع ممتلكاتهم على انها اضافة قيمة إلى تجارب المسافر. ""This study aims to highlight digital marketing as a reality that has imposed itself strongly in the global market for the tourism industry, by valuing the role it plays in generating innovative digital future strategies, through which it is possible to develop a vision for the development and development of the tourism industry and thus activating and revitalizing this sector while preparing it for the transformation of the pattern of digital tourism. In the applied study, we relied on two leading international hotels in the hospitality sector and concluded that for the development of the tourism industry it is necessary to create a well-thought-out, customized and accurate marketing strategy through social media, because effective social communication can bring participation and superior customer service to support customers, Given the high costs of customer acquisition through traditional online advertising, investors in the tourism industry must truly evaluate the return on investment to attract new consumers into a loyalty ring that may actually lose the consumer retention footprint, and hoteliers must produce always-on content that is not only relevant subject, but based on the peculiarities of a local destination, creating links to position their properties as a valuable addition to the traveler's experiences. "
ماستر تسويق
Keywords: التسويق الرقمي، صناعة السياحة، فندق الماريوت، فندق الهيلتون.; digital marketing, tourism industry, the Marriott Hotel, the Hilton Hotel